Pandemic swine influenza virus (H1N1): A threatening evolution - Khanna, Madhu (Springer-Verlag, 2010)
“Survival of the fittest” is an old axiom laid down by the great evolutionist Charles Darwin and microorganisms seem to have exploited this statement to a great extent. The ability of viruses to adapt themselves to the changing environment has made it possible to inhabit itself in this vast world for the past millions of years. Experts are well versed with the fact that influenza viruses have the capability to trade genetic components from one to the other within animal and human population. In mid April 2009, the Centers for Disease Control and Prevention and the World Health Organization had recognized a dramatic increase in number of influenza cases. These current 2009 infections were found to be caused by a new strain of influenza type A H1N1 virus which is a re-assortment of several strains of influenza viruses commonly infecting human, avian, and swine population. This evolution is quite dependent on swine population which acts as a main reservoir for the reassortment event in virus. With the current rate of progress and the efforts of heath authorities worldwide, we have still not lost the race against fighting this virus. This article gives an insight to the probable source of origin and the evolutionary progress it has gone through that makes it a potential threat in the future, the current scenario and the possible measures that may be explored to further strengthen the war against pandemic.